2020
DOI: 10.17352/ijvsr.000061
|View full text |Cite
|
Sign up to set email alerts
|

The impact of Gibe III hydroelectric dam on the situation of livestock diseases with particular emphasis on bovine trypanosomosis in Southern Ethiopia

Abstract: This study was initiated to explore the impact of Gibe III dam on the situation of livestock diseases with emphasis on trypanosomosis in upstream and downstream districts. Focus group discussions with 15 groups each with 6-20 members were conducted using participatory research approach. Data were collected through simple ranking, proportional piling and matrix scoring. Level of agreement among groups analyzed was determined by Kendell's coeffi cient concordance (W). Proportional piling revealed that bovine try… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The finding also agreed with focus group discussion conducted in the same area, the knowledge of a swollen lymph node, cough/salivation, fever, loss of appetite, and diarrhea also were considered as clinical manifestations. 28 Studies in the Orma community in Kenya reflected similar clinical signs for chronic trypanosomosis infection but hemorrhage and sudden death reported to the acute form of the disease. 29 Comparable knowledge was mentioned in the agro-pastoralist community in Lamwat and Kwale, Kenya.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The finding also agreed with focus group discussion conducted in the same area, the knowledge of a swollen lymph node, cough/salivation, fever, loss of appetite, and diarrhea also were considered as clinical manifestations. 28 Studies in the Orma community in Kenya reflected similar clinical signs for chronic trypanosomosis infection but hemorrhage and sudden death reported to the acute form of the disease. 29 Comparable knowledge was mentioned in the agro-pastoralist community in Lamwat and Kwale, Kenya.…”
Section: Discussionmentioning
confidence: 96%
“…26 Almost all respondents agreed the occurrence of trypanosomosis and its cause of transmission depends on season mainly in the long rainy season which is in agreement with other research work. 22,28 Seasonal observation in the same study site showed a significantly high prevalence of trypanosomosis and high tsetse and biting fly apparent density observed in the rainy season. 18 Knowledge on signs and transmission of trypanosomosis by farmers observed in the high tsetse challenge area, 27 agreed with current finding; 44% of farmers agreed tsetse fly accompanied with the river, grazing site and wet season are the main cause of trypanosomosis.…”
Section: Species Identified G Pallidipes G Fuscipesmentioning
confidence: 89%
See 1 more Smart Citation